Problem-Based Learning as an Effort to Improve Junior High School Students’ Learning Mastery and Communication Skills - Tias Ernawati; Resti Nur Chotimah (Universitas Sarjanawiyata Tamansiswa, 2022)
The objectives of this research were to determine the Problem-Based Learning model that enhances natural sciences minimum mastery criteria of learning achievement and communication skills at Junior high school Taman Dewasa Jetis, Yogyakarta. This research was Classroom Action Research. This research, each cycle contains planning, implementation, observation, and reflection. The cycle was completed in the second cycle because indicator of success had been achieved. Research instruments include teacher and students’ observation sheets, sciences learning achievement tests and communication skills questionnaires. The results show that students could reach the natural sciences minimum mastery criteria of learning achievement and an increase in communication skills was worth considering. In the first cycle, students’ learning achievement rose 6.75 points above the natural science minimum mastery criteria; the second cycle rose 18.8 points above the natural science’s minimum mastery criteria. Communication skills in the first cycle increased by 3.65%, and in the second cycle increased by 10.57%.